Efficacy and Safety of Bcl-2 Inhibitor Venetoclax in Hematological Malignancy: A Systematic Review and Meta-Analysis of Clinical Trials - Li, Qingfang; Cheng, Li; Shen, Kai; Jin, Hongyu; Li, Hui; Cheng, Yuan; Ma, Xuelei (Frontiers in Pharmacology, 2019)
Abstract Background ：B cell leukemia/lymphoma-2(BCL-2) protein is an important part of apoptotic pathway, which is overexpressed in chronic lymphocytic leukemia (CLL)cells, non-Hodgkin lymphoma (NHL) cells and myeloma cells. Venetoclax (ABT-199/GDC-0199) is a highly selective bioavailable inhibitor of BCL-2 protein, which is more effective and less valid against BCL-xL in BCL2-dependent leukemia and lymphoma cell. Method ：We searched PubMed database using retrieval keyword Venetoclax, ABT-199 or GDC-0199 and investigated the data of the involved articles. Considering variability in different studies, the overall response rate (ORR) was collected to access the efficacy. Meanwhile, Adverse events (AEs) were summarized and event rates were calculated to access the safety. Results ：When patients were treated with venetoclax monotherapy, the most common AEs were nausea, diarrhea, neutropenia, fatigue and thrombocytopenia and neutropenia. In addition, thrombocytopenia, anemia, febrile neutropenia and leukopenia appeared more common considering the severe AEs (defined as grade ≥3 AEs). Though the occurrence of thrombocytopenia was relatively high, it was not the most severe type. When compared with patients treated with venetcoalx and other drugs, nausea, diarrhea and thrombocytopenia were still the most common AEs occurrence in the patients of all the grade. The overall event rate was 73%, which is quite satisfactory. Conclusion ： Venetoclax is a mild and efficient drug in treating advanced hematological malignancy which is specially fit for the CLL patients with del[17p], and AEs are well-tolerable. Few tumor lysis syndrome (TLS) occurred after taking the drugs. The AEs aroused by venetovlax and combination are well-tolerable. Therefore, the use of venetoclax monotherapy or its combination with other therapies is desirable in hematological malignancy.